Role of biosimilar introduction on insulin glargine prices: a retrospective analysis in 28 European countries - David Beran; Margaret Ewen; Mario Raviglione; Tido von Schoen-Angerer; Davide Morolla (BMJ Open)
Objective Quantify insulin glargine prices following the market introduction of biosimilars. Examine price levels and price changes for originator and biosimilars, by country.Methods Retrospective quantitative analysis using insulin glargine pricing data, both of the originator product and its biosimilars. Segmented regression analysis using a dual-model approach: pooled and country-specific.Setting 28 European countries using data from the European Medicine Price Database for the period 2013–2023.Main outcome measures Price variations between countries were analysed to assess trends and correlations before and after biosimilar market entry.Results In the 28 countries studied, cost of insulin glargine underwent a median 21.6% decrease overall in the last decade (p<0.001). In 2022, the median price was €9.0 for the originator (first to market) Lantus (IQR €8.1–€10.4), €8.9 for the biosimilar Abasaglar (IQR €7.6–€10.1) and €7.0 for the biosimilar Semglee (median €7.0; IQR €6.8–€7.5). The originator price was higher than biosimilars (p=0.009). Biosimilar market entry was associated with an overall significant price reduction of the originator, both immediately after entry (p<0.001) and in the long-term postentry (p<0.001). No significant correlation was observed between the price of insulin and the countries’ economic indicators.Conclusion This is the first study to show the price trend of insulin glargine and its correlation with the introduction of biosimilars, in Europe. A significant price reduction of the originator was observed after biosimilars entered the market. The median cost of biosimilars was lower than the originator, although with substantial differences between individual countries and producers.